ESA INTEGRAL and Cataclysmic Variables - Strobl, Jan; Hudec, René; Simon, Vojtéch; Hroch, Filip; Working Group, INTEGRAL CP CVs (Одеські астрономічні публікації, 2017)
The satellite INTEGRAL is ESA project operating since January 2003. It is dedicated to high energy astronomy. INTEGRAL is able to detect and perform astrometry, photometry and spectroscopy of sources from X-ray to gamma-ray regime (nominal range of sensitivity is 15 keV - IOMeV) via its multiple instruments. Moreover, it’s equipped with an X-ray event monitor and a small optical telescope to provide a full multi-wavelength satellite observatory. Mission abilities are interesting for any object emitting Gamma-rays or X-rays. One of them are Cataclysmic Variables (CVs), which are X-ray and some of them probably even gamma-ray sources. Cataclysmic variables were included into ” Core Science Programme” of INTEGRAL and even though they are not a main mission goal (and INTEGRAL will not focus on observing them directly, with some exceptions), we assume to have good results from the periodical surveys. This contribution should introduce the mission INTEGRAL and our intentions in field of related CVs research.